Redefining Malaysia's printing landscape: insights from Porter's CAN Model / Muhammad Yusuf Masod and Siti Farhana Zakaria - Masod, Muhammad Yusuf; Zakaria, Siti Farhana (Universiti Teknologi MARA, Perlis, 2024)
Malaysia's burgeoning printing industry, while showcasing potential, grapples with challenges that constrain its growth and global reach, underscoring the need for a deep and structured assessment. This pivotal study is designed to unpack the competitiveness of the Malaysian printing sector within the vast expanse of the global market, with a spotlight on the commercial printing segment. It revolves around the central inquiry: "Which critical factors mold the competitiveness of Malaysia's printing industry, and how can insights from Porter's Competitive Advantage of Nations (CAN) model illuminate them?" Anchored in the renowned Porter's CAN model, the research undertakes a multifaceted analysis of industry pillars, including intricate demand patterns, supply chain dynamics, prevailing competition, and the overarching influence of government directives. Data, meticulously sourced from 2015-2019 through national agencies and global institutions, forms the bedrock of this systemic examination. The study reveals that Malaysia stands fortified by assets like adept labor, contemporary infrastructure, and cost-effective energy provisions. Yet, it's not devoid of challenges, notably, the lag in embracing cuttingedge production tech and the absence of razor-sharp competitive strategies. However, the surge in both domestic and international demand sketches a promising trajectory. Beyond validating the robustness of the CAN model, the study weaves a tapestry of insights for industry stakeholders. It underscores the pivotal role of agile government interventions and the pressing mandate to integrate digital innovations. The findings beckon a targeted strategy to navigate and neutralize identified pitfalls, amplifying the industry's global resonance. While the study carves a panoramic landscape, its primary reliance on secondary datasets is its Achilles' heel. Still, it emerges as an invaluable compass for industry stakeholders, directing strategic investments and policy recalibrations to elevate the global stature of Malaysia's printing industry.